Haemodialysis: hospital or home?. Issue 1060 (12th November 2013) - Power, Albert; Ashby, Damien
Abstract: Healthcare costs associated with the provision of dialysis therapy are escalating globally as the number of patients developing end-stage renal disease increases. In this setting, there has been heightened interest in the application and potential benefit of home haemodialysis therapies compared with the conventional approach of thrice weekly, incentre treatments. Increasingly, national healthcare systems are financially incentivising the expansion of home haemodialysis programmes with observational studies demonstrating better patient survival, superior control of circulating volume and blood pressure, greater patient satisfaction and lower running costs compared with incentre dialysis. Nonetheless, increasing the prevalence of home haemodialysis is challenged by the technological complexity of conventional dialysis systems, the need for significant adaptations to the home as well as suboptimal clinician and patient education about the feasibility and availability of this modality. In addition, enthusiasm about frequent as well as nocturnal (extended-hours) haemodialysis has been tempered by results from the recent Frequent Haemodialysis Network randomised controlled trials comparing these schedules with a conventional incentre regime. An increasing emphasis on empowering patient choice and promoting self-management of chronic illness is a powerful driver for the expansion of home haemodialysis programmes in the UK and internationally.